Asian and Pacific Cosmopolitans
XX, 237 p.
Keywords: This new collection of essays explores questions of subjectification, selfhood and identity in the contemporary Asia Pacific, examining the way that migrant lives express the complex interplay of local and global processes in the post-Cold War era, and collectively questioning the novelty of the 'global age' in this region.